2006
DOI: 10.1590/s0100-83582006000400001
|View full text |Cite
|
Sign up to set email alerts
|

Seed longevity of red rice ecotypes buried in soil

Abstract: -Red rice is a troublesome weed in irrigated rice production and is spread through contaminated commercial rice seed and machinery. Seed dormancy is a major trait for red rice. Studies were carried out at two locations to determine red rice seed longevity in the soil of several ecotypes from four US states. Five months after burial near Beaumont, Texas only three ecotypes had viable seed (<1%) when buried at 5 cm, but 9 ecotypes had viable seed after two years when buried at 25 cm. At the thirty-sixth month af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 29 publications
2
35
0
2
Order By: Relevance
“…Furthermore, research showed that secondary dormancy did not occur in both weedy rice and rice cultivars; weedy rice seeds have the ability to survive at low temperatures in winter and afterward re-establish their population. This attribute is said to be ecotype dependent and influenced by other factors, such as burial depth, soil type, climate, moisture, cultivation practices, magnitude of seed production, and dormancy level (Noldin et al, 2006), even though the lower limit temperature for weedy rice germination was the same as for rice (10 °C). Seed dormancy longevity had the advantage of early colonization of rice fields by the weedy rice variant.…”
Section: Weedy Rice Biology and Competition With Cultivated Ricementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, research showed that secondary dormancy did not occur in both weedy rice and rice cultivars; weedy rice seeds have the ability to survive at low temperatures in winter and afterward re-establish their population. This attribute is said to be ecotype dependent and influenced by other factors, such as burial depth, soil type, climate, moisture, cultivation practices, magnitude of seed production, and dormancy level (Noldin et al, 2006), even though the lower limit temperature for weedy rice germination was the same as for rice (10 °C). Seed dormancy longevity had the advantage of early colonization of rice fields by the weedy rice variant.…”
Section: Weedy Rice Biology and Competition With Cultivated Ricementioning
confidence: 99%
“…Hence, weedy rice is well adapted to extreme temperatures. Additionally, it can emerge from greater depths than cultivated rice (Noldin et al, 2006). All these attributes account for the ability of weedy rice to compete well with rice cultivars.…”
Section: Weedy Rice Biology and Competition With Cultivated Ricementioning
confidence: 99%
See 1 more Smart Citation
“…Esse revolvimento pode contribuir tanto para o enterramento de sementes em maiores profundidades quanto para o posicionamento daquelas antes enterradas próximas à superfície. Noldin et al (2006) verificaram que a longevidade de sementes de arroz-vermelho (Oryza sativa) enterradas em camada de solo mais superficial (até 5 cm) foi muito reduzida quando comparada à daquelas enterradas em maior profundidade (12 a 25 cm). Quando as sementes não dormentes retornam à superfície, provavelmente germinam, mas as dormentes poderão retornar para uma profundidade maior, pelo cultivo posterior (Cavers & Benoit, 1989).…”
Section: Riqueza De Espéciesunclassified
“…This indicates that just a few years of distinct management between areas is not enough to promote changes at the soil seed bank in a way that the most problematic weed species are eliminated from the area. However, after a few years the distinct management would probably promote immediate changes at the composition of weed species at the soil surface -species not favored by the management would be present at the soil seed bank but would have to enter in a dormant or quiescent state, waiting for proper conditions for germination (Noldin et al, 2006).…”
Section: Resultsmentioning
confidence: 99%